THE IMPLEMENTATION OF GREEN BANKING AND BOPO ON FINANCIAL PERFORMANCE IN BANKING COMPANIES IN INDONESIA - Abnaina, Elma; Analisa , Analisa; Sawaluna, Desi (Yayasan Education and Social Center, 2025)
Performance of a banking company can be seen from its profitability level. Banking companies strive to maximize profits in carrying out their business activities. The greater the profitability, the greater the profit. Conversely, if profitability is low, the profit will also be low. The goal points referred to as the Sustainable Development Goals (SDGs) are indicators of the implementation of sustainable business, one of which is in the economic sector. The implementation and disclosure of green banking practices and the calculation of the BOPO ratio in a company can be considered economically efficient if it can save production costs to achieve maximum profit using the panel data method (Random Effect Model/REM). The results of this study indicate that green banking has a positive and significant negative effect on profitability at banks in Indonesia.